2017
DOI: 10.1021/acs.accounts.6b00602
|View full text |Cite
|
Sign up to set email alerts
|

CO2–Water–Rock Wettability: Variability, Influencing Factors, and Implications for CO2 Geostorage

Abstract: Carbon geosequestration (CGS) has been identified as a key technology to reduce anthropogenic greenhouse gas emissions and thus significantly mitigate climate change. In CGS, CO is captured from large point-source emitters (e.g., coal fired power stations), purified, and injected deep underground into geological formations for disposal. However, the CO has a lower density than the resident formation brine and thus migrates upward due to buoyancy forces. To prevent the CO from leaking back to the surface, four … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

14
232
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1

Relationship

4
2

Authors

Journals

citations
Cited by 310 publications
(246 citation statements)
references
References 64 publications
14
232
0
Order By: Relevance
“…However, although it is well established that brine salinity can vary widely between prospective storage reservoirs, there is a knowledge gap in terms of how this can influence storage efficiency. Importantly, experimental data showed that water salinity has a significant impact on the water‐CO 2 ‐rock contact angle θ (i.e., rock wettability) . For example, Arif et al .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, although it is well established that brine salinity can vary widely between prospective storage reservoirs, there is a knowledge gap in terms of how this can influence storage efficiency. Importantly, experimental data showed that water salinity has a significant impact on the water‐CO 2 ‐rock contact angle θ (i.e., rock wettability) . For example, Arif et al .…”
Section: Introductionmentioning
confidence: 99%
“…This effect is caused by a better surface charge screening at higher salinities. Mechanistically, cations move to the negative surfaces charges and shield them, thus reducing the surface potential and surface polarity, which leads to a dewetting of the surface . Furthermore, salinity affects water viscosity (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Al-Anssari et al [129] investigated the influence of pressure on the wettability of calcites treated with and without nanoparticles in the presence of CO 2 to account for pressure variation with injection depth. An increase in pressure with increase in contact angle occurred for all surfaces tested which is attributed to an increase in intermolecular interactions between CO 2 and calcite, which increased significantly with increasing CO 2 density thus an implication of a reduction in structural and residual trapping capacities at reservoir conditions [126][127][128][130][131][132][133]. At ambient condition, oil-wet calcite was weakly CO 2 -wet (115 θa -0.1 MPa and 323 K) and strongly CO 2 -wet at storage conditions (148 θa -20 MPa and 323 K) -the high contact angle is an indication of possibilities of CO 2 leakage.…”
Section: Co 2 Storage and Leakage Inhibitionmentioning
confidence: 91%
“…These curves were built using experimental data . Intermediate‐wet conditions were chosen, as this is the most likely wettability scenario in CO 2 ‐brine deep saline aquifer systems . In addition, rock wettability has a significant effect on the residual water and gas saturations .…”
Section: Methodsmentioning
confidence: 99%
“…The effectiveness of the trapping mechanisms depends on various geological and hydraulic parameters, including geological reservoir heterogeneities, caprock properties, CO 2 ‐rock wettability, reservoir temperature, wettability heterogeneity, and brine salinity . Moreover, although many geological parameters cannot be changed for a particular site, it has been shown that intelligent selection of CO 2 injection technology (e.g.…”
Section: Introductionmentioning
confidence: 99%